2018
DOI: 10.14260/jemds/2018/858
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Single-Dose of Dexamethasone in Reduction of Pain, Nausea and Vomiting After Laparoscopic Cholecystectomy- A Randomised Controlled Trial

Abstract: BACKGROUND Dexamethasone is an available and cheap drug and has low complications. There are not enough studies on antiemetic and analgesic effects of dexamethasone after laparoscopic cholecystectomy. The aim of this study was to assess the efficacy of single-dose of dexamethasone on Postoperative Pain (POP) and Nausea and Vomiting (PONV) in the patients undergoing laparoscopic cholecystectomy in northern Iran. MATERIALS AND METHODS This randomised controlled trial was conducted on 140 patients who were candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Dexamethasone inhibits the inflammatory response by blocking factors such as bradykinin, prostaglandin, and leukotrienes, which result in a decreased level of inflammation and reduction of the signs and symptoms including pain [14]. A study by Emami et al suggested that pre-operative dexamethasone (8 mg) reduces the incidence of PONV, pain, and fatigue after laparoscopic cholecystectomy and concluded that the employed regimen is safe and without apparent side effects [15]. Fujii and Nakayama found that dexamethasone (8 mg) is effective in reducing the rate of PONV and analgesic requirements in adult Japanese patients undergoing middle ear surgery [16].…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone inhibits the inflammatory response by blocking factors such as bradykinin, prostaglandin, and leukotrienes, which result in a decreased level of inflammation and reduction of the signs and symptoms including pain [14]. A study by Emami et al suggested that pre-operative dexamethasone (8 mg) reduces the incidence of PONV, pain, and fatigue after laparoscopic cholecystectomy and concluded that the employed regimen is safe and without apparent side effects [15]. Fujii and Nakayama found that dexamethasone (8 mg) is effective in reducing the rate of PONV and analgesic requirements in adult Japanese patients undergoing middle ear surgery [16].…”
Section: Discussionmentioning
confidence: 99%